2016
DOI: 10.1159/000452474
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effect of the Traditional Japanese Herbal Medicine, Hochuekkito, against Influenza A Virus via Autophagy in vitro

Abstract: Background: Hochuekkito (HKT), a traditional Japanese herbal medicine, enhances the immunity of elderly or weak individuals. It is also known to have preventive effects against influenza clinically. However, the detailed mechanisms of the preventive effects have not been clarified. We examined the relationship between the preventive effects of HKT and autophagy, a known stress response and quality control mechanism, using Madin-Darby canine kidney cells and influenza A/PR/8/34 (H1N1) virus. Methods: The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Next, we investigated the effects of HET on energy homeostasis in aged FR mice, because recent studies have demonstrated the potential of HET to induce autophagy 16 , 17 and restore metabolic homeostasis 18 . The results in Table 1 demonstrate the capacity of HET and its ingredients to induce autophagy as assessed by HEK293 autophagy-reporter cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we investigated the effects of HET on energy homeostasis in aged FR mice, because recent studies have demonstrated the potential of HET to induce autophagy 16 , 17 and restore metabolic homeostasis 18 . The results in Table 1 demonstrate the capacity of HET and its ingredients to induce autophagy as assessed by HEK293 autophagy-reporter cells.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies have reported that HET improves fatigue, lack of energy, and low body temperature in adult patients with appetite loss 37 , QOL and immunological status of elderly patients with weakness 38 , and nutritional status in elderly patients with chronic obstructive pulmonary disease 39 . Several studies carried out in vitro have demonstrated the potential of HET to restore metabolic homeostasis 18 and promote autophagy 16 , 17 . We confirmed that HET and 9 of its chemical ingredients derived from astragalus root, jujube, ginger, and ginseng induced autophagy in studies featuring reporter cells; these studies suggest that these compounds may contribute to the inductive effects of HET.…”
Section: Discussionmentioning
confidence: 99%
“…Recent scientific research, on the contrary, has indicated that the combinatorial effect of mixed EAHM preparation can be particularly effective for complicated disorders, such as PN, autoimmune disease, degenerative disease, and cancer, which do not react well with single compound-based modern pharmaceutics [121][122][123][124]. As an example, recent research has demonstrated that EAHM can be used in large-scale public health emergencies, such as COVID-19 or preventive medicine using modern analytical tools, such as synthetic biology, data mining, and genomics [123,[125][126][127][128]. Future studies need to be conducted to identify the properties of EAHM to be utilized in actual drug discovery.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…This may be one of the reasons for the pathological changes of osteomalacia, osteosclerosis, and osteoporosis in fluorosis. Light chain 3 alpha (LC3A) and Beclin 1 have been used as markers to detect autophagy activity ( Ding et al, 2016 ). Apoptosis is regulated by many related genes, such as B-cell lymphoma 2 (Bcl-2) and Bcl-2-associated X (BAX) ( Anesan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%